Gene Expression and Methylation Levels of PCSK9 Gene in Iraqi Patients with Coronary Artery Disease (Baghdad Science Journal, 2023)
The expression of the Proprotein Convertase Subtilisin/Kexin Type 9 gene (PCSK9) is inextricably related to lipid levels and a risk of atherosclerotic coronary artery disease (ASCAD). The present study aims to measure the quantity of PCSK9 gene expression and the effect of methylation on its expression level taking part in the pathogenesis of acute coronary artery disorder.A current study included 150 subjects from the Iraqi population, 100 ASCAD patients and 50 healthy controls. The concentration of PCSK9 in each serum sample was determined by the ELISA technique, the expression levels of the PCSK9 gene in whole blood were estimated by RT-qPCR – Quantitative Reverse Transcription PCR method, and DNA methylation level detection in PCSK9 gene by using High Resolution Melting Analysis (HRM) technique.The expression level of the PCSK9 gene was 6.06 ± 1.84 in ASCAD patients group compared with a control group 1.00 ±0.19. That indicates the up-regulation of the PCSK9 gene in patient with atherosclerosis. In addition, the PCSK9 concentration was higher in patient group in comparison to the healthy controls group P= < 0.01. However, PCSK9 methylation levels, a highly significant distinction between the two study groups p=0.002. In conclusion, serum PCSK9 levels are associated with coronary artery lesions as shown in receiver operating characteristic (ROC) analysis. Suggests that, serum PCSK9 might be a good indicator of coronary artery disease development.